Early effects of fluoxetine on emotional processing: implications for adolescent depression - Capitao, L (2014)
Depression in adolescence is a major health problem, associated with poor psychological function and key risk factors both for later illness and suicidal behaviours. The antidepressant fluoxetine is commonly used in this population and it is shown to have a favourable benefit-to-risk profile. However, controversy still exists about the use of antidepressants in young people and there is little research focusing on underlying mechanisms of wanted and unwanted actions in this group. This doctoral thesis aims to investigate, for the first time, the acute effects of fluoxetine on emotional processing, using a combination of behavioural and neuroimaging techniques. The aim is to achieve a greater understanding of the mechanisms underlying fluoxetine use in depressed adolescents, in light of differences seen in their clinical presentation and response to antidepressant drugs. In the first study (Chapter Two), a single dose of fluoxetine was shown to decrease the recognition of anger in a sample of young adult volunteers, an effect not previously seen in acute studies of older participants. This effect may be particularly relevant for the treatment of adolescent depression, in which symptoms of anger and irritability are often prominent. Beyond this, fluoxetine was shown to increase the recognition of positive vs. negative facial information, and also exerted an anxiolytic-like influence, eliminating the emotion-potentiated startle effect. However, no influence was seen in measures of attentional vigilance to threat. In an attempt to overcome methodological limitations of this study, a paradigm was developed that is particularly sensitive to the detection of automatic biases towards threatening information (Chapter Three). Chapter Four describes a neuroimaging study with depressed adolescents, in which a single dose of fluoxetine was found to reduce amygdala activity in response to anger. Early changes in amygdala activity to fear correlated with decreased symptoms of anxiety and depression in the first 7-10 days of treatment. Chapter Five explores the effects of acute fluoxetine in a sample of high trait anger males. This study replicated the finding that fluoxetine acts to increase the recognition of positive information, whilst showing preliminary evidence for a reduction in attentional vigilance to angry faces. Overall, fluoxetine was found to decrease the processing of anger across studies. This effect was seen alongside a broader influence on positive vs. negative information and anxiolytic-like properties. Together, these results indicate that fluoxetine has direct effects on processes that are especially relevant to adolescent depression and suggest a potential cognitive mechanism for the efficacy of this particular antidepressant in adolescent patients.